2006
DOI: 10.1093/rpd/nci518
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quartz OSL and isothermal TL measurements on Chinese loess

Abstract: The reliability of equivalent doses (De) from Chinese loess, measured using isothermal thermoluminescence (ITL) is tested. Dose calculations use the single-aliquot regenerative-dose (SAR) procedure. Despite good reproducibility of laboratory-induced signals and negligible response at zero dose, a significant overestimation of De is observed, compared with OSL measurements. Measurement of a known laboratory dose administered after optical bleaching, but before any heating, demonstrates that the first heating du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…3), such as thermally-transferred OSL (Wang et al, 2006) and isothermal TL (ITL) (e.g. Buylaert et al, 2006).In light of our results, a promising candidate in luminescence thermochronology is feldspar.Photostimulation of feldspars can be achieved using both visible and infrared wavelengths (Hütt et al, 1988).The IRSL signal from feldspars is particularly useful for dating because it has several advantages over the OSL signal of quartz. Firstly, it is commonly observed that the IRSL signal from feldspar does not saturate until much higher doses than those found for the quartz OSL signal; thus it has the potential for extending the time frame for thermo-chronology.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…3), such as thermally-transferred OSL (Wang et al, 2006) and isothermal TL (ITL) (e.g. Buylaert et al, 2006).In light of our results, a promising candidate in luminescence thermochronology is feldspar.Photostimulation of feldspars can be achieved using both visible and infrared wavelengths (Hütt et al, 1988).The IRSL signal from feldspars is particularly useful for dating because it has several advantages over the OSL signal of quartz. Firstly, it is commonly observed that the IRSL signal from feldspar does not saturate until much higher doses than those found for the quartz OSL signal; thus it has the potential for extending the time frame for thermo-chronology.…”
mentioning
confidence: 73%
“…3), such as thermally-transferred OSL (Wang et al, 2006) and isothermal TL (ITL) (e.g. Buylaert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SAR (Murray & Wintle 2000), SARA (Mejdahl & Bøtter‐Jensen 1994) is not strictly a ‘single‐aliquot’ technique, because it requires at least two aliquots to yield a D e value; however, the benefit of SARA is that it can be used to obtain reliable D e values irrespective of the sensitivity changes which might occur during measurement of an aliquot. Buylaert et al (2006) concluded that measuring ITL using a SARA technique potentially offered a large increase in the dose range compared to measurements made using OSL, and showed consistency between the SARA‐ITL and SAR‐OSL D e values in regions where the OSL signal is not saturated. However, in contrast to Choi et al (2006), the use of a SAR‐ITL protocol gave significantly higher D e values than using SAR‐OSL, due to large sensitivity changes occurring during the first heating applied to measure the natural signal (Buylaert et al 2006).…”
Section: Future Developments In Luminescence Dating Of Loess Depositsmentioning
confidence: 93%
“…Buylaert et al (2006) concluded that measuring ITL using a SARA technique potentially offered a large increase in the dose range compared to measurements made using OSL, and showed consistency between the SARA‐ITL and SAR‐OSL D e values in regions where the OSL signal is not saturated. However, in contrast to Choi et al (2006), the use of a SAR‐ITL protocol gave significantly higher D e values than using SAR‐OSL, due to large sensitivity changes occurring during the first heating applied to measure the natural signal (Buylaert et al 2006). Interestingly, use of the SARA‐ITL in the study by Huot et al (2006) did not give results which were in agreement with known age samples; this study is worth mentioning in this review because, although it was not conducted on loess, it noted the important point that a SARA approach is inherently less useful in the strongly non‐linear region of the growth curve, which is of course the region of interest for extending the dating range.…”
Section: Future Developments In Luminescence Dating Of Loess Depositsmentioning
confidence: 93%
See 1 more Smart Citation